Do Anti-Phage Antibodies Persist after Phage Therapy? A Preliminary Report - Marzanna Łusiak-Szelachowska; Ryszard Międzybrodzki; Paweł Rogóż; Beata Weber-Dąbrowska; Maciej Żaczek; Andrzej Górski (MDPI AG, 2022)
Phages are immunogenic and may evoke an immune response following their administration. Consequently, patients undergoing phage therapy (PT) produce phage-neutralizing serum antibodies. The clinical significance of this phenomenon for the success or failure of the therapy is currently unclear. Interestingly, even a strong anti-phage humoral response does not exclude the success of PT. On the other hand, it cannot be ruled out that phage-antibody complexes may be trapped in tissues and organs causing injury and late complications of PT. Therefore, patients should be monitored for the presence of serum antibodies and therapy discontinued if their level is high. Our preliminary data suggest that the kinetics of the disappearance of those antibodies may vary from patient to patient and in some cases may take more than a year.